Daniel 3 as satirical comedy - Nel, Marius (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The tale in Daniel 3 is told to people living in the second century BCE whose lives were threatened by the Syrian Antiochus IV Epiphanes when they disobeyed his command to forsake their religion as a desperate measure of quenching recurrent Jewish rebellion. After reading the tale the Jews could not help but laugh at worldly kings who preposterously cut down the Jewish God, only to find out that he is in charge of the world, and that God has predetermined the destination of their kingdoms. The article describes the humorous and satirical elements in the tale in order to explain its impact on the initial readers. The fantastical elements of surviving a fiery furnace and a mighty king bowing before the god of a people conquered by his power, told tongue in cheek, can only be explained sensibly as satire and comedy.